Advanced exergy analysis of reverse Brayton cryocooler for 10 kW cooling capacity at 65 K. Issue 1 (1st May 2022) - Kumar Dhillon, Aman; Ghosh, Parthasarathi
Abstract: A reverse Brayton cryocooler is gaining attention as an intermediate and large-scale cooling device for many cryogenic applications such as liquefaction of natural gas, hydrogen, cooling of high-temperature superconducting devices. The present work is an inclusive analysis of reverse Brayton cryocooler by splitting the exergy destruction approach, known as advanced exergy analysis. The study aims to find the scope of improvement in the component by categorizing the exergy destruction as avoidable and unavoidable. Therefore, it is a more potent tool, compared to split exergy methods, to identify the scopes for enhancement of the thermodynamic performance of the equipment. In this work, a thermodynamic model based on the split exergy approach (conventional exergy analysis) is developed using Aspen HYSYS®. The conventional exergy analysis quantifies the exergy destruction in each component of the cryocooler. The advanced exergy analysis quantified the avoidable exergy destruction as 61 % of total exergy destruction in the system. The results of the analysis suggest ways to improve the performance of components of the reverses Brayton cryocooler from thermodynamic and design aspects. The recommendation and approach adopted in the present work, although it has been applied for reverse Brayton refrigerator, can be very useful for the research and design engineer working in the field of energy systems in general.